(V, Nb)-doped half Heusler alloys based on {Ti, Zr, Hf}NiSn with high ZT. (1st June 2017) - Rogl, G.; Sauerschnig, P.; Rykavets, Z.; Romaka, V.V.; Heinrich, P.; Hinterleitner, B.; Grytsiv, A.; Bauer, E.; Rogl, P.
Abstract: Half Heusler alloys are among the most promising materials for thermoelectric generators as they can be used in a wide temperature range and their starting materials are abundant and cheap, the latter as long as no hafnium is involved. For Sb-doped Ti0.5 Zr0.25 Hf0.25 NiSn Sakurada and Shutoh in 2008 have published ZTmax  = 1.5 at 690 K, a value that hitherto was never reproduced independently. In this paper we successfully prepared Ti0.5 Zr0.25 Hf0.25 NiSn with ZTmax  = 1.5, however, at higher temperature (825 K). As the main goal is to produce hafnium – free half Heusler alloys, we investigated the influence of niobium or vanadium dopants on Tix Zr1−x NiSn0.98 Sb0.02, reaching ZTs > 1.2 and thermal-electric conversion efficiencies up to 13.1%. For Hf-free n-type TiNiSn-based half Heusler alloys these values are unsurpassed. In order to further improve our thermoelectric materials our study is completed by electrical resistivity and thermal conductivity data in the low temperature range but also by mechanical properties (elastic moduli, hardness) at room temperature. The electrical properties have been discussed in comparison with DFT calculations. Graphical abstract: Image 1